Implementasi Manajemen Keuangan dalam Pengelolaan Uang Saku sebagai Penunjang Hasil Belajar Siswa - Amatullah Noor Hanifah; Supri Wahyudi Utomo; Liana Vivin Wihartanti (STKIP PGRI SITUBONDO, 2022)
The student personal financial management system implemented at SMP Ibnu Batutah is a rare system where children are not allowed to bring their own pocket money and manage it on hand. This study aims to determine the application of financial management in the allowance management system at SMP Tahfidz Ibnu Batutah and its impact on student learning outcomes. This research was conducted in the first semester of the 2019/2020 academic year using qualitative methods and by comparing the average monthly expenses of students with the average learning outcomes obtained by students in one semester. The data collection technique used was direct interviews due to this pandemic through online interviews with several informants as well as by direct observation and retrieval of related documents such as pocket money and student learning outcomes.The results obtained from this study are that the pocket money system at SMP Tahfidz Ibnu Batutah which does not allow students to bring their own pocket money actually supports student learning success. This relationship is also supported by the record of student spending which is also directly proportional to the learning outcomes they receive.